The Rise of Spanish-Language Filmmaking : Out from Hollywood's Shadow, 1929-1939. - Jarvinen, Lisa (Latinidad., 2012)
In The Rise of Spanish-Language Filmmaking, Lisa Jarvinen focuses specifically on how Hollywood lost a lucrative international Spanish-speaking audience between 1929 and 1939, along with talent it had carefully nurtured in the United States. Employing studio records from Warner Bros., Fox Films, and United Artists, Jarvinen examines the lasting effects of the transition to sound on both Hollywood practices and cultural politics in the Spanish-speaking world. Using case studies based on archival research in the United States, Spain, and Mexico, she shows how language, as a key marker of cultura.